For an education with no hope. Issue 2 (23rd August 2020) - Zipory, Oded
Abstract: Most of the literature in educational research, and in philosophy of education specifically, has been clearly appealing to hope in its various forms, in attempts to bring it back, improve it and have more of it. This paper wishes to explore a different terrain. I ask whether there can be a worthwhile education that does not require hope, and I suggest that even when hope remains a commendable attribute of education, the strict prohibition on hopelessness in education should be rejected for there is much to be gained from embracing hope's opposite—despair. Firstly, I discuss hope's faults and drawbacks, focusing on the reasons for its rejection in ancient Greece and on its privatisation and commodification in contemporary capitalist society. Here, hope's connection to transcendence and the secular attempts to overcome it will be examined. Secondly, following the conceptualisation of despair by political theorist Robyn Marasco (2015), I reassess the dialectics of hope and despair and highlight the role of hopelessness in energising and enlivening critique. Finally, reading in Martin Luther King's famous 'I have a dream' speech, I suggest that a pedagogy of despair can accommodate presentism and even, despite its name, bring about a particular dialectics of hope.